Strain-free GeSn nanomembranes enabled by transfer-printing techniques for advanced optoelectronic applications - Tai, Yeh-Chen (2021)
GeSn alloys have emerged as promising materials for silicon-based optoelectronic devices. However, the epitaxy of pseudomorphic GeSn layers on a Ge buffer is susceptible to a significant compressive strain that significantly hinders the performance of GeSn-based photonic devices. Herein, we report on a new strategy to produce strain-free GeSn nanomembranes for advanced optoelectronic applications. The GeSn alloy was grown on a silicon-on-insulator substrate using Ge buffers, and it has a residual compressive strain. By transfer-printing the GeSn/Ge/Si multi-layers, followed by etching the Si template and the Ge buffer layers, respectively, the residual compressive strain was completely removed to achieve strain-free GeSn layers. A bandgap reduction was also observed as a result of strain relaxation. Furthermore, theoretical analysis was performed to evaluate the effect of strain relaxation on the GeSn-based optoelectronic devices. The proposed approach offers a practical and viable method for preparing strain-free GeSn alloys for advanced optoelectronic applications.